2009
DOI: 10.1103/physrevlett.102.115002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Electron Transport and Shear Alfvén Activity in the National Spherical Torus Experiment

Abstract: We report the observation of a correlation between shear Alfvén eigenmode activity and electron transport in plasma regimes where the electron temperature gradient is flat, and thus the drive for temperature gradient microinstabilities is absent. Plasmas having rapid central electron transport show intense, broadband global Alfvén eigenmode (GAE) activity in the 0.5-1.1 MHz range, while plasmas with low transport are essentially GAE-free. The first theoretical assessment of a GAE-electron transport connection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 22 publications
7
98
2
Order By: Relevance
“…Microtearing modes have since been found in conventional aspect ratio tokamak plasmas [19,20], and a nonlinear microtearing mode saturation theory estimate of χ e was found to be consistent with NSTX measurements [21]. Electron heat transport was observed to increase dramatically with rising beam power in the core of NSTX, where fast particle instabilities were observed and thermal temperature gradients were too low to drive transport via the usual mechanisms [22]. Microtearing modes, fast particle instabilities, and sonic flows will not be addressed further in this paper.…”
Section: Confinement Transport and Gyrokinetic Studies Of Stsmentioning
confidence: 66%
“…Microtearing modes have since been found in conventional aspect ratio tokamak plasmas [19,20], and a nonlinear microtearing mode saturation theory estimate of χ e was found to be consistent with NSTX measurements [21]. Electron heat transport was observed to increase dramatically with rising beam power in the core of NSTX, where fast particle instabilities were observed and thermal temperature gradients were too low to drive transport via the usual mechanisms [22]. Microtearing modes, fast particle instabilities, and sonic flows will not be addressed further in this paper.…”
Section: Confinement Transport and Gyrokinetic Studies Of Stsmentioning
confidence: 66%
“…69(a). 163 The radial electron temperature profile instead broadens with the NBI power, indicating greatly enhanced electron thermal diffusivity in the core with the applied NBI power as shown in Fig. 69(b).…”
Section: Anomalous Electron Thermal Energy Transport By Gaesmentioning
confidence: 94%
“…162 In addition, there are energetic-particle-driven global and compressional Alfv en eigenmodes (GAE and CAE), which can also affect power deposition and electron energy transport in the plasma core region. 163 In terms of drive and stabilization mechanisms, electron beta b e and collisionality e/i are important parameters as illustrated in Fig. 62.…”
Section: A Motivation For St Researchmentioning
confidence: 99%
“…The high frequency instability observed in NSTX [2,3] had k ∥ qR ≫ 1. Assuming that this condition is satisfied, we approximate the Bessel function as J…”
Section: Energy Channelling and Electron Heat Transport (Quasilinear mentioning
confidence: 99%
“…In experiments on both W7-AS and NSTX the instabilities affected the heat transport but had no visible influence on the particle transport. In addition, NSTX experiments have shown that the effect of the Alfvénic activity on the plasma heat transport can differ at different locations: the calculated heat conductivity coefficient increases with injected power in the core region and decreases at the periphery [2,3]. Another peculiarity of the NSTX data is that the anomalous heat transport correlates only with high frequency instabilities (0.5 ÷ 1.1 MHz).…”
Section: Introductionmentioning
confidence: 99%